John Calvin's Christological Assertion of Word Authority in the Context of Sixteenth Century Ecclesiological Polemics - Morrison, John D. (Scottish journal of theology, 1992)
The late medieval synthesis reflected in the Fourth Lateran Council (1215) generally and in the doctrine of transubstantiation in particular established an understanding of the nature of the church and authority that was to be varied and wide in its effects. Transubstantiation as doctrine and as coalescor of Church worship laid the groundwork for a particularly formative understanding of the ekklesia of Christ. It issued in a view of immanental, divine authority and grace that would come to manifest itself in the indulgences, the treasury of merits, invocation of saints, relics, etc. To be critical of the Mass was to bring into question the entire hierarchy of the Church and its authority on earth. In this context of strong ecclesiological authority, God was reckoned primarily as immanent and immediate through the papal head. In the face of this development, John Calvin asserted that Christ, as center of all true Christian reality, is the necessary focus and the preeminent authority in and to the Church through the Word of God, the Scriptures.